Challenges and Opportunities in the Seed Delivery, Scaling, and Extension Strategies for Smallholders in South Asia - Nayak, Swati; Hossain, Mosharaf; Singh, Varsha; Nath, Anirban; Mohapatra, Subhasmita (Springer, 2025)
The agricultural landscapes of South Asia, intricately woven into the fabric of daily life, rely heavily on the efficacy of seed supply, scaling, and extension processes. Smallholder farmers, the bedrock of the region’s agricultural economy, have historically exhibited resilience and ingenuity, sustaining communities through generations. However, they are confronted with emerging issues requiring innovative solutions and responses by researchers and policymakers. This chapter addresses the pressing issues of seed quality and availability, the successful scaling of agricultural practices, and the effectiveness of extension programs designed to empower farmers with essential skills and knowledge. It explores the complex interplay between seed supply, scaling practices, and extension services. Through an in-depth review, it identifies the barriers to quality seed flow and proposes viable solutions to stimulate sustainable development. The objective is to provide insights for policymakers, practitioners, and researchers on targeted interventions that empower smallholder farmers and ensure a resilient future for South Asia’s agriculture.